2010
DOI: 10.1111/j.1365-2389.2010.01257.x
|View full text |Cite
|
Sign up to set email alerts
|

Phytolith transport in soil: a laboratory study on intact soil cores

Abstract: Column experiments on phytolith transport were conducted to assess the partial contributions of water percolation and earthworm activity to phytolith transport in loamy and sandy soils. Six intact cores of a loamy sandy Haplic Cambisol and nine cores of a silty loamy Stagnic Luvisol were excavated. With the Luvisol, three treatments were perfomed: a percolation treatment with periodic irrigation, but without earthworms, a percolation and earthworm treatment with periodic irrigation and earthworms (Aporrectodea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 50 publications
2
15
0
9
Order By: Relevance
“…In the “reference” situation the temperate landscape is dominated by deciduous climax forests. These systems show tight recycling of Si in the soil‐plant system [ Sommer et al , ; Cornelis et al , ], and dissolved Si in soil water can be taken up by plants and/or incorporated in clays [ Cornelis et al , , , ; Vandevenne et al , ]—“stage 1.” Biogenic Si (in litter) does not form a long‐term pool in our soils, and this is in line with other studies from temperate zones where a sharp drop in BSi and/or phytoliths is observed at the transition between organic and mineral horizons [ Barão et al , ; Fishkis et al , ]. Deforestation and land use cultivation with moderate to complete removal of biomass will then decrease BSi stocks in soils, in particular when not compensated by Si fertilizers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the “reference” situation the temperate landscape is dominated by deciduous climax forests. These systems show tight recycling of Si in the soil‐plant system [ Sommer et al , ; Cornelis et al , ], and dissolved Si in soil water can be taken up by plants and/or incorporated in clays [ Cornelis et al , , , ; Vandevenne et al , ]—“stage 1.” Biogenic Si (in litter) does not form a long‐term pool in our soils, and this is in line with other studies from temperate zones where a sharp drop in BSi and/or phytoliths is observed at the transition between organic and mineral horizons [ Barão et al , ; Fishkis et al , ]. Deforestation and land use cultivation with moderate to complete removal of biomass will then decrease BSi stocks in soils, in particular when not compensated by Si fertilizers.…”
Section: Discussionsupporting
confidence: 90%
“…Biogenic Si (in litter) does not form a long-term pool in our soils, and this is in line with other studies from temperate zones where a sharp drop in BSi and/or phytoliths is observed at the transition between organic and mineral horizons [Barão et al, 2014;Fishkis et al, 2010]. Deforestation and land use cultivation with moderate to complete removal of biomass will then decrease BSi stocks in soils, in particular when not compensated by Si fertilizers.…”
Section: 1002/2014gb005049supporting
confidence: 91%
“…Low phytolith concentration in very coarse soils or in very active bioturbation soils has also been shown to be the result of phytolith translocation (e.g. Fiskish et al, 2010). These authors showed size dependence on phytolith percolation by water, with phytoliths with a size diameter of 5μm being the most susceptible to move downward In our study, if phytolith translocation had occurred in our samples with low number of phytoliths (limestone fynbos, coastal thicket, strandveld vegetation types) then we would expect to not see small morphotypes, such as GSSC rondels and saddles or spheroids psilates and rugulates, what is not the case.…”
Section: Phytolith Deposition and Preservation In Modern Soilsmentioning
confidence: 99%
“…For instance, transport of bacteria and colloids in soils is widely documented for dimensions up to 10 µm (McKay et al ., ; Jacobsen et al ., ; Semenov et al ., ; Wang et al ., ). On the other hand, percolation of phytolith and nematodes (dimensions spanning from <5 up to 500 µm) through soil columns is found negligible or null (Planchon et al ., ; Fishkis et al ., , ).…”
Section: Introductionmentioning
confidence: 99%